PENDAMPINGAN PENGUATAN LITERASI MELALUI PROGRAM POJOK BACA DI SMP INTEGRAL HIDAYATULLAH - Moch Haris; Faelasup (CV. ADIBA AISHA AMIRA, 2024)
In the future, the reading and writing skills of the younger generation will be crucial to improving their abilities. This reading corner has several objectives, namely increasing interest in reading and supporting a culture of literacy in the community. This program aims to describe the process of implementing literacy activities at SMP Integral Hidayatullah, describe the factors that support and hinder literacy activities at SMP Integral Hidayatullah, and the results of implementing literacy activities at SMP To describe SMP Integral Hidayatullah in terms of student character. The approach used in this program is a qualitative approach that utilizes data collection techniques through interviews, observation and documentation. The results of this study are determined by using various reading facilities such as the school library and reading corner. Some remedial programs such as Thursday Reading are also carried out as habituation activities outside the classroom, and reading 15 minutes before learning is a habituation activity that occurs in the classroom. The participation of all stakeholders in learning activities is a supporting factor for the success of literacy activities in the school but the relatively long distance to the local library is an inhibiting factor for literacy activities. Consistent student reading activities and the ability to apply the results of reading in classroom activities provide strong evidence that school-based literacy activities have a positive impact on students' reading skills.